2007
DOI: 10.1093/eurheartj/sum022
|View full text |Cite
|
Sign up to set email alerts
|

Exercise echocardiography in pulmonary hypertension

Abstract: Doppler echocardiography plays a key role in the detection of pulmonary hypertension, the leading cause of right ventricular (RV) dysfunction. Reliable estimates of pulmonary pressures and cardiac output (CO) can be obtained at rest, allowing for screening and diagnosis of pulmonary arterial hypertension (PAH), a group of diseases characterized by increased pulmonary vascular resistance progressing to RV failure and death. However, these resting indices poorly correlate with symptoms, exercise response, and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Similarly, PAP measured only at rest fails to detect a significant percentage of patients with exercise‐induced PAH (EIPAH). EIPAH is a poorly understood entity 4–12. Some believe that EIPAH is an early and more treatable phase that precedes resting PAH, whereas others suggest that it may be a stable variant of the disease 5,6,13–15.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, PAP measured only at rest fails to detect a significant percentage of patients with exercise‐induced PAH (EIPAH). EIPAH is a poorly understood entity 4–12. Some believe that EIPAH is an early and more treatable phase that precedes resting PAH, whereas others suggest that it may be a stable variant of the disease 5,6,13–15.…”
Section: Introductionmentioning
confidence: 99%
“…The upper normal limit of the response in normally trained individuals seems to be higher than commonly assumed. 9 The number of examined individuals in our study is high compared to other studies with a comparable focus that investigated mixed groups of normally trained subjects and athletes made up of 20 3 to 40 individuals. 1 Our study group has a sufficient distribution of age and gender to allow conclusions to be drawn concerning adolescents and young adults.…”
Section: Discussionmentioning
confidence: 78%
“…2 International guidelines define the normal upper limits of pulmonary arterial systolic pressure at rest, but there is a general uncertainty about the upper limits for both pulmonary and right ventricular systolic pressures during exercise. 9,10 A value of 40 millimetres of mercury, or in some papers 45 millimetres of mercury, is proposed as the upper normal limit during exercise. 2,3,11 Recent studies, however, have shown an abnormal response of right ventricular systolic pressure above 45 millimetres of mercury during exercise in healthy, normal individuals, 12 and also in healthy carriers of mutations in the bone morphogenetic protein receptor type 2 gene.…”
mentioning
confidence: 99%
“…23 The exercise echocardiogram is a reliable noninvasive technique to detect latent or exerciseinduced PH not evident by standard resting Doppler echocardiography. 24 In normal subjects, exercise PASP should be <43 mmHg 12 ; however, in patients aged 50 years or older, 47% surpassed a pulmonary artery mean pressure (PAMP) of 30 mmHg during maximal exercise. 25 Due to very different peak exercise PAP cutoffs, it is difficult to calculate the real prevalence of PH in SSc patients and its clinical relevancy.…”
Section: Discussionmentioning
confidence: 99%